GREEN KAMPONG: URBAN POVERTY INITIATIVE PROGRAM FOR TRANSIENT POOR FAMILY IN BENGKULU, INDONESIA - Santoso, Djonet; Hendrastiti, Titiek Kartika (ASIAN JOURNAL FOR POVERTY STUDIES (AJPS), 2017)
Urban poverty is still a thorny issue in almost all cities in Indonesia. Urban poverty is grouped into two different characteristics: chronic and transient. Chronic poverty experienced by those who are under the poverty line, while transient poverty experienced by those who are around the poverty line. Unlike the chronic group that is often the target of poverty reduction policies, transient group is often overlooked. They do not exist in the scheme of poverty reduction programs. In fact, the number of transient poor population is about 46 percent, compare to the chronic population that is only 11%. With almost having similar condition with the chronic group, transient group is characterized by unstable income, large spending on food, limited access to drinking water, live in the surrounding slums, and having a low quality sanitation. The question is, how the survival strategy of the neglected transient is able to cope with their difficult life. And the most important thing, what program should be done by the government to deal with transient poverty? This paper will discuss the economic living conditions of transient poor families in urban Bengkulu City, Indonesia, reviews their survival strategy, initiatives and experiences. It also talks about ongoing Green Kampong project promoted by the University of Bengkulu that integrates incomes generation efforts for the transient poor and the commitment of environmental protection through the vegetables planting in every idle land in the kampong area.